ROOT MORPHOLOGY OF MAIZE LINES WITH CONTRASTING DROUGHT RESISTANCE UNDER THREE TOXIC LEVELS OF ALUMINUM - MAGALHÃES, PAULO CÉSAR; SOUZA, THIAGO CORRÊA DE; CANTÃO, FERNANDO RODRIGO DE OLIVEIRA; PADILHA, FÁBIO ANDRADE (REVISTA BRASILEIRA DE MILHO E SORGO, 2012)
The aim of this work was to evaluate attributes of dry mass and root morphology characteristics in lines with contrasting drought resistance (two tolerant and two sensitive) from the Breeding Program of CNPMS (Maize and Sorghum National Research Center), under three levels of aluminum saturation (low, intermediate and high). A randomized blocks design was used, with two replications for each level of Al-saturation. Evaluations were performed at 14 and 28 days after sowing. Root morphology was assessed using the WinRhizo image analysis system. Significant differences were observed for dry matter attributes between lines, especially the sensitive ones. Concerning root morphology, the drought resistant lines presented higher total root length (RL), root surface area (SA), root volume (RV) and greater very thin roots length (VTRL). In conclusion, lines selected for drought resistance can be indirectly selected for aluminum tolerance. <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif";} > <! [endif] >The objective of the present work was to evaluate attributes of dry mass and root morphology characteristics in lines with contrasting drought resistance (two tolerant and two sensitive) from the Breeding Program of Maize and Sorghum National Research Center (EMBRAPA), under three levels of aluminum saturation (low, intermediate and high). A randomized blocks design was used, with two replications for each level of Al-saturation. Evaluations were performed at 14 and 28 days after sowing. Root morphology was assessed using the WinRhizo image analysis system. Significant differences were observed for dry matter attributes between lines, especially the sensitive ones. Concerning root morphology, the drought resistant lines presented higher total root length (RL), root surface area (SA), root volume (RV) and greater very thin roots length (VTRL). In conclusion, lines selected for drought resistance can be indirectly selected for aluminum tolerance.</sp > The objective of the present work was to evaluate attributes of dry mass and root morphology characteristics in lines with contrasting drought resistance (two tolerant and two sensitive) from the Breeding Program of Maize and Sorghum National Research Center (EMBRAPA), under three levels of aluminum saturation (low, intermediate and high). A randomized blocks design was used, with two replications for each level of Al-saturation. Evaluations were performed at 14 and 28 days after sowing. Root morphology was assessed using the WinRhizo image analysis system. Significant differences were observed for dry matter attributes between lines, especially the sensitive ones. Concerning root morphology, the drought resistant lines presented higher total root length (RL), root surface area (SA), root volume (RV) and greater very thin roots length (VTRL). In conclusion, lines selected for drought resistance can be indirectly selected for aluminum tolerance.<-->